25 Years of sensory drive: the evidence and its watery bias. Issue 4 (7th June 2018) - Cummings, Molly E; Endler, John A; ,
Abstract: It has been 25 years since the formalization of the Sensory Drive hypothesis was published in the American Naturalist (1992). Since then, there has been an explosion of research identifying its utility in contributing to our understanding of inter- and intra-specific variation in sensory systems and signaling properties. The main tenet of Sensory Drive is that environmental characteristics will influence the evolutionary trajectory of both sensory (detecting capabilities) and signaling (detectable features and behaviors) traits in predictable directions. We review the accumulating evidence in 154 studies addressing these questions and categorized their approach in terms of testing for environmental influence on sensory tuning, signal characteristics, or both. For the subset of studies that examined sensory tuning, there was greater support for Sensory Drive processes shaping visual than auditory tuning, and it was more prevalent in aquatic than terrestrial habitats. Terrestrial habitats and visual traits were the prevalent habitat and sensory modality in the 104 studies showing support for environmental influence on signaling properties. An additional 19 studies that found no supporting evidence for environmental influence on signaling traits were all based in terrestrial ecosystems and almost exclusively involved auditory signals. Only 29 studies examined the complete coevolutionary process between sensory and signaling traits and were dominated by fish visual communication. We discuss biophysical factors that may contribute to the visual and aquatic bias for Sensory Drive evidence, as well as biotic factors that may contribute to the lack of Sensory Drive processes in terrestrial acoustic signaling systems.